Numerical study on thermal performance of water flow in a twisted duct heat exchanger - Rashed, Musaab K.; Jehhef, Kadhum Audaa; Badawy, Faris Ali (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a numerical study of heat transfer through a downstream annulus using water as the working fluid within the laminar flow region. The annulus consisted of an outer twisted square duct and an inner circular pipe. A three-dimensional formulation was used to solve the Navier-Stokes equations numerically for the laminar flow system with a low Reynolds number.
Keywords: mixed convection; twisted square duct; heat exchanger; laminar flow